Preparo de emulsões com óleos essenciais para aplicação em tratamento de sementes no controle in vitro de Fusarium oxysporum f. sp. Lycopersici - Pretto, Matheus Milani (2021)
Plants that produce essential oils are rich in secondary metabolites, which have the potential to control pathogens that cause economic losses in the agricultural sector and can become an efficient alternative in the control of diseases, including those caused by soil fungi. Therefore, the objective of the study was to evaluate the effect of essential oils, in the in vitro control, in two isolates of Fusarium oxysporum f. sp. Lycopersici race 3, through the application of pure oil and in the preparation of emulsions for the treatment of tomato seeds. The experiments were conducted at the Federal University of Santa Maria/Frederico Westphalen campus, from May 2020 to April 2021. In experiment 1, the performance of nine pure essential oils (A, B, C, D, E, F, G) was evaluated., H and I) in the growth of two isolates of the pathogenic fungus under study. Essential oils, in doses of 0.0; 0.3; 0.6; 0.9; 1,2; 1.5; 1.8; 2.1; 2.4 mL.L-1 were introduced into PDA medium at 50 ºC and, after solidification in a Petri dish, a mycelial disc of the pathogen was inoculated in the center of the dish. Fungal growth assessments were performed over a 10 day period. After this period, it was found that the best results were obtained with essential oil B, as it required the lowest doses to completely inhibit fungal growth. Essential oils C, D, E and F also showed control over the pathogen, but with higher doses. Essential oils A, G, H and I did not show total control of the pathogen at the doses studied in this work. In experiment 2, the effect of emulsions prepared with three essential oils at doses of 2.5; 5.0; 10.0 mL.L-1, diluted in 25%, 30% and 75% on the growth of the pathogen isolates and its effect on the germination and vigor of tomato seeds. The antifungal potential of the emulsions was verified with their introduction into PDA medium at 50 ºC and, after solidification in a Petri dish, the pathogen's mycelial disk was inoculated in the center of the dish. The effect of these emulsions on the seeds was verified with their application in the form of seed treatment. All doses and concentrations of the studied emulsions showed an inhibitory effect on the in vitro development of Fusarium oxysporum f. sp. lycopercisi, race 3. The doses of the emulsions, in their respective concentrations, did not interfere in the germination and vigor of tomato seeds, indicating the potential of this technology for the development of a product for the control of Fusarium oxysporum f. sp. Lycopersici race 3, in the form of seed treatment.